SYNTHESIS, EVALUATION AND DOCKING STUDIES OF NOVEL FORMAZAN DERIVATIVES AS AN ENOYL-ACP REDUCTASE INHIBITORS - Thangavelu, Prabha; Cellappa, Selvinthanuja; Thangavel, Sivakumar (International Journal of Pharmacy and Pharmaceutical Sciences, 2018)
Objective: To synthesize, evaluate and performing the docking studies of novel formazan derivatives as enoyl-ACP reductase inhibitors. Materials: In the present investigation, a series of formazans (Ia-d) were synthesized by stirring aryl diazonium salts solution with Schiff's base at 0-5˚C for 2 h. The intermediate azomethine (Schiff base) itself was synthesized by condensation of para aminobenzoic acid with dimethylamino benzaldehyde in presence of a glacial acetic acid as a catalyst. The antimicrobial activity was done for these synthesized compounds by cup plate method. Moreover, the antimicrobial activity was further confirmed by its molecular docking approach study by using Molecular Operating Environment (MOE) 2009.10 software. Results: In the present study all the synthesized compounds (Ia-Id) showed the enhanced zone of inhibition against S. aureus, B. subtilis, E. coli and S. typhi (5±0.12 to 12±0.45) whereas, the antifungal activity against A. niger and C. albicans were showed the zone of inhibition in the range of 9±0.51 to 12±0.43 when compared to that of the standard drug. Further the docking study reveals that, only three of the formazan compounds under observation (Ia, Ib and Ic) have higher binding affinity with the receptors enzymes enoyl-ACP reductase, which is in the narrow range of binding energy for the protein PDB: 1C14 is-24.4598 to-23.9377 kcal/mol, which shows the further confirmation of these formazan compounds as better microbial inhibitor. Conclusion: Therefore our present report shows that formazans could be the potential drug candidate that inhibits the microbial activity by interacting and inhibiting the enoyl-ACP reductase enzyme which is confirmed by its both in vitro antimicrobial study and as well as from its docking study.